PENGARUH PENGGUNAAN APLIKASI KAHOT! TERHADAP KETERAMPILAN BERBICARA DALAM PENYAJIAN BERITA SISWA - Alya Revalina Achmad; Anshari; Muhammad Saleh (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the effect of using the Kahoot! application on speaking skills in news presentation among students in class XI.7 at SMA Negeri 3 Makassar. The type of research used was quantitative research with a One Group Pretest-Posttest design. The data collection technique was carried out through a speaking skills test divided into a pretest and posttest. The population of this study was all students of class XI.7 of SMA Negeri 3 Makassar, while the research sample was 36 students of class XI.7, determined using the total sampling technique. Data analysis was performed using descriptive statistical analysis and inferential statistical analysis. The results showed that students' speaking skills in news presentation before the implementation of the Kahoot! application were very poor, with a pretest average score of 47.74, which was in the range of 0–49. After the implementation of the Kahoot! application, the students' speaking skills improved significantly and were categorized as good, with a posttest average score of 74.35, which falls within the range of 70–84. Based on the results of the paired sample t-test using SPSS, a Sig. (2-tailed) value of 0.000 < 0.05 was obtained, indicating that H₀ was rejected and H₁ was accepted. Thus, it can be concluded that there is a significant effect of the Kahoot! application on speaking skills in news presentation among students in class XI.7 at SMA Negeri 3 Makassar.